Explorer of Enceladus and Titan (E2T): Investigating ocean worlds' evolution and habitability in the solar system - Mitri, Giuseppe; Postberg, Frank; Soderblom, Jason M.; Wurz, Peter; Tortora, Paolo; Abel, Bernd; Barnes, Jason W.; Berga, Marco; Carrasco, Nathalie; Coustenis, Athena; Paul de Vera, Jean Pierre; D'Ottavio, Andrea; et al. (Planetary and space science, 2018)
Titan, with its organically rich and dynamic atmosphere and geology, and Enceladus, with its active plume, both harbouring global subsurface oceans, are prime environments in which to investigate the habitability of ocean worlds and the conditions for the emergence of life. We present a space mission concept, the Explorer of Enceladus and Titan (E2T), which is dedicated to investigating the evolution and habitability of these Saturnian satellites. E2T is proposed as a medium-class mission led by ESA in collaboration with NASA in response to ESA's M5 Cosmic Vision Call. E2T proposes a focused payload that would provide in-situ composition investigations and high-resolution imaging during multiple flybys of Enceladus and Titan using a solar-electric powered spacecraft in orbit around Saturn. The E2T mission would provide high-resolution mass spectrometry of the plume currently emanating from Enceladus' south polar terrain and of Titan's changing upper atmosphere. In addition, high-resolution infrared (IR) imaging would detail Titan's geomorphology at 50-100 m resolution and the temperature of the fractures on Enceladus' south polar terrain at meter resolution. These combined measurements of both Titan and Enceladus would enable the E2T mission scenario to achieve two major scientific goals: 1) Study the origin and evolution of volatile-rich ocean worlds; and 2) Explore the habitability and potential for life in ocean worlds. E2T's two high-resolution time-of-flight mass spectrometers would enable resolution of the ambiguities in chemical analysis left by the NASA/ESA/ASI Cassini-Huygens mission regarding the identification of low-mass organic species, detect high-mass organic species for the first time, further constrain trace species such as the noble gases, and clarify the evolution of solid and volatile species. The high-resolution IR camera would reveal the geology of Titan's surface and the energy dissipated by Enceladus' fractured south polar terrain and plume in detail unattainable by the Cassini mission.